Exporting the Policy - International Data Transfer and the Role of Binding Corporate Rules for Ensuring Adequate Safeguards - Maksó, Bianka (Pécs journal of international and European law, 2016)
Personal data plays a key role in our digital age. The legislator is working on making the data controller interested in protecting personal data by self-regulation, so Binding Corporate Rules were enacted as the latest legal institution for ensuring adequate safeguards in case of international data transfers. In this study after a brief description of the strategic value of personal data the author makes an attempt to introduce BCR and their legal background within the rules of international data transfer in order to give an introduction on how EU data protection policy can affect data controllers in third countries.